Careful Evaluation of Cosyntropin Dose in the Diagnosis of Adrenal Insufficiency - Musurakis, Clio (J Endocr Soc, 2021)
Introduction: The use of the 250μg cosyntropin dose or otherwise called high-dose ACTH test is the gold standard test for diagnosis of primary adrenal insufficiency. The 1μg dose test or the low-dose test is mostly reserved for diagnosis of secondary adrenal insufficiency. Careful consideration of the results produced during the diagnostic process is imperative to avoid mislabeling of patients with a disease that requires lifelong treatment. Case Report: This is the case of a 45-year-old female with a history of asthma and psoriasis who presented with emesis. Home medications included monthly TNF-alpha inhibitor injections for psoriasis, triamcinolone acetonide topical spray and budesonide-formoterol inhaler. On admission, she also had nausea, chills and diaphoresis, as well as palpitations, lightheadedness, and shortness of breath. When she arrived at the ER, vitals were remarkable for low blood pressure. Labs were unremarkable except for CMP concerning for anion gap metabolic acidosis, hyponatremia, and hypokalemia. A random serum cortisol was 6.4 mcg/dL, which was relatively low. ACTH was within normal range. Due to concern for adrenal insufficiency, a 1μg cosyntropin test was performed which showed a peak cortisol concentration of less than 18 mcg/dL. As the response was assessed as suboptimal, endocrinology was consulted to offer a treatment plan for steroids. However, the test was repeated using the gold standard 250μg cosyntropin dose and the patient then showed an adequate response and she was not started on steroids. Conclusions: This is a case that demonstrates how the 250 μg ACTH or high-dose stimulation test should be used for diagnosis of primary adrenal insufficiency (AI), as it is the gold standard. The 1 μg ACTH or low-dose stimulation test can be used for diagnosis of primary AI but only when the high dose test is not available. On the other hand, the 1 μg ACTH stimulation test has been shown to be more sensitive than the 250 μg test in diagnosing secondary adrenal insufficiency. When using the most appropriate test correctly, the clinician can only then offer the patient the best treatment strategies. Our patient did not require chronic replacement therapy. The steroids in this case could have harmed the patient as chronic administration could cause adrenal gland suppression.